CONSTRUCTION OF THE CONVERGENCE COMMUNICATION MODEL: HARMONIZING SOCIAL AND DIGITAL CAPITAL IN INTERGENERATIONAL AGRICULTURAL COLLABORATION - Agus Kristian; Eko Purwanto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The global agricultural sector is currently facing a serious threat in the form of a farmer regeneration crisis amid the ambition to achieve sustainable food security. Although Smart Farming technology is available, its adoption rate is hindered by a sharp communication gap between senior farmers and the younger generation. This study aims to construct a convergence communication model capable of harmonizing the social capital of senior farmers and the digital capital of the younger generation. The method used is qualitative with a Systematic Literature Review approach. The analysis was conducted on various reputable literatures from Scopus, Web of Science, and Sinta databases within the last ten years. The results show a divergence in characteristics between the bonding social capital of senior farmers, which tends to be exclusive, and the digital capital of the younger generation, which is technocentric but lacks social relations. As a solution, this study constructs a Convergence Communication Model that integrates reverse mentoring strategies and cyclical dialogue to achieve mutual understanding. The implications of this model are the acceleration of inclusive farmer regeneration, increased resource efficiency based on the green economy, and the strengthening of national food stability through the synergy of resilient intergenerational assets.